Biocompatibility, Degradation Behavior, and Mechanical Properties of Magnesium Alloy Plates In Vivo - Yongping Wang; Qingqing Qin; Xiaorong Liu; Qiangqiang Li; Huaibin Zhang; Dubin Yang; Yao Jiang (Applied Bionics and Biomechanics)
The magnesium alloy was made into orthopedic steel plates to repair tibial fractures of New Zealand white rabbits and to explore the biocompatibility, degradation behavior, and mechanical properties of the magnesium alloy plates in repairing fractures in vivo. Fifty-four rabbits were randomly divided into experimental, control, and sham-operated groups. Tibial fractures in the experimental and the control groups were fixed with magnesium alloy and titanium alloy plates, respectively, and only bone tunnels were established without any implants in the sham-operated group. The concentrations of serum alanine transaminase, creatinine (CREA), creatine kinase (CK), and magnesium ion were measured before and 1 day, 1, 2, 4, 8, and 16 weeks after operation, respectively, to evaluate the biocompatibility of magnesium alloy plates. The corrosion products and components were observed using a scanning electron microscope with an energy-dispersive spectroscopy system, and the corrosion rate was observed by weight loss testing. Then the degradation behavior of magnesium alloy plate was analyzed. Analysis of mechanical properties of magnesium alloy plates was done by four-point bending tests. There were no statistically significant differences in serum alanine transaminase, CREA, or CK at each time point among the three groups (P>0.05). The degradation behavior of the magnesium alloy plates increased with the longer implantation time. The four-point bending test results indicated that the mechanical properties of magnesium alloy plates decreased gradually during the degradation. The results showed that magnesium alloy plates implanted into rabbit tibias degrade gradually with the implantation time, and the mechanical properties of the magnesium alloy weaken gradually during the degradation. Meanwhile, the magnesium alloy plate had excellent biocompatibility and biosafety in the process of degradation in vivo.